2018
DOI: 10.1038/s41467-017-02782-9
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution spatiotemporal transcriptome mapping of tomato fruit development and ripening

Abstract: Tomato (Solanum lycopersicum) is an established model for studying fruit biology; however, most studies of tomato fruit growth and ripening are based on homogenized pericarp, and do not consider the internal tissues, or the expression signatures of individual cell and tissue types. We present a spatiotemporally resolved transcriptome analysis of tomato fruit ontogeny, using laser microdissection (LM) or hand dissection coupled with RNA-Seq analysis. Regulatory and structural gene networks, including families o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
271
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 285 publications
(282 citation statements)
references
References 81 publications
10
271
0
1
Order By: Relevance
“…An AP2/ERF transcription factor orthologous to Arabidopsis WRI3 , was identified as the master regulator targeting 17 genes, including those encoding pyruvate kinase, pyruvate dehydrogenase, acetyl-coenzyme A carboxylase, carboxyl transferase and acyl carrier proteins ( Supplementary Table 13). Coexpression of the tomato WRI3 with lipid metabolism genes in the epidermis of developing fruit (Shinozaki et al, 2018) suggested its potential function in tissue-specific regulation of lipid biosynthesis, thus contributing to fruit cuticular wax accumulation (Fig. 4c).…”
Section: Genome-wide Mapping Of Eqtlsmentioning
confidence: 99%
“…An AP2/ERF transcription factor orthologous to Arabidopsis WRI3 , was identified as the master regulator targeting 17 genes, including those encoding pyruvate kinase, pyruvate dehydrogenase, acetyl-coenzyme A carboxylase, carboxyl transferase and acyl carrier proteins ( Supplementary Table 13). Coexpression of the tomato WRI3 with lipid metabolism genes in the epidermis of developing fruit (Shinozaki et al, 2018) suggested its potential function in tissue-specific regulation of lipid biosynthesis, thus contributing to fruit cuticular wax accumulation (Fig. 4c).…”
Section: Genome-wide Mapping Of Eqtlsmentioning
confidence: 99%
“…Recent developments have focused on the importance of genome-wide methylation status (Manning et al, 2006;Zhong et al, 2013) and chromatin histone marks (Dong et al, 2017) for the expression of ripening genes, discussed later. The view that has emerged is of an interacting network of transcription factors and hormone biosynthesis and signaling genes that orchestrate a cascade of events, culminating in the expression of many hundreds, perhaps thousands, of genes that contribute to the ripening process (M. C. Liu et al, 2015Giovannoni et al, 2017;Shinozaki et al, 2018). One new twist to the story has been the demonstration that, although many ERFs do respond to ethylene (M. C. Liu et al, 2015Deng et al, 2018), others actually respond to auxin , whereas some are regulated by both hormones .…”
Section: New Phytologistmentioning
confidence: 99%
“…Another important issue is: in which cells do specific genes or hormones exert their effects? A gene involved in generating a gradient of ripening gene expression through the fruit has been identified (Nguyen et al, 2014) and data on cellular localization of transcripts are becoming available (Shinozaki et al, 2018). There are some indications that the response in fruit starts in the locule gel or the seeds and MADS-RIN and NAC-NOR are switched on earlier in this region (Giovannoni et al, 2017).…”
Section: Reviewmentioning
confidence: 99%
“…For the comparison of different biological systems, we selected the significantly enriched gene ontologies from our N. benthamiana RNAseq experiment (p and q values <0.05) and compared their Z-score values with those obtained from the analysis of published RNAseq data of tomato fruit ripening and Arabidopsis leaf senescence. In particular, we used the RPM values of the total pericarp at mature green (MG), light ripe (LR) and red ripe (RR) stages (Shinozaki et al, 2018) and the FPKM values of the 16D and 30D senescence stages (Woo et al, 2016). DEGs resulting from LR/MG, RR/MG and 30D/16D comparisons were filtered as described above for N. benthamiana crtB/GFP.Student's t-tests were used for the rest of statistical analyses using GraphPad Prism 5.0a (GraphPad Software).…”
Section: Statistical Analysesmentioning
confidence: 99%